High temperature interactions between coal ash and MgO-based refractories in lime kiln conditions. (15th June 2023) - Wagri, Naresh Kumar; Carlborg, Markus; Eriksson, Matias; Ma, Charlie; Broström, Markus; Andersson, Britt M.
Highlights: Coal ash infiltrates into MgO-based refractories under lime kiln conditions. Temperature has a dominating effect on infiltration during short exposure times. Infiltration depth was higher in refractories with lower porosity. Typical Mg-silicate corrosion products forms in the refractories. Abstract: Magnesium oxide (MgO)-based refractories are commonly used in quicklime and cement rotary kilns. At the high temperatures in the kiln burn zone, the infiltration of molten fuel ash into the refractory can occur. Subsequent chemical interactions can cause refractory wear that inflicts high maintenance costs and loss of production. To improve refractory reliability, it is necessary to increase the understanding of the interactions between fuel ash slag and refractory liner materials. Three commercially available MgO-based refractory materials were exposed to coal ash at 1200 °C and 1400 °C for between 15 and 60 min under a CO2 -rich gaseous environment. Hot slag from the coal ash infiltrated the refractories and the infiltration depths were estimated with scanning electron microscope with energy dispersive X-ray spectroscopy. Based on detailed elemental and microstructure analyses, the interactions between ash and refractory were examined. Molten silicates infiltrated the refractory through grain boundaries and pores into depths of up to 2.8 mm. Powder X-ray diffraction of the exposed refractory samples indicated that MgO grains reacted with SiO2 -containing phases to form Mg2 SiO4 . This was identified as a corrosion product whose formation was supported by thermochemical equilibrium calculations. Elevated Mg content was found in the ash residue on top of the samples, indicating the dissolution or dislocation of refractory components. In addition, phases such as MgO were identified in the ash residue.